P1.005 Evaluation of Cytokines and Matrix Metalloproteinases Genes Expression in Genital Organs After Vaginal Exposure to Chlamydia Muridarum. (13th July 2013) - Marangoni, A; Cavallini, C; Foschi, C; Nardini, P; Aldini, R; D'Errico, A; Rosini, F; Cevenini, R
Abstract : Background: Although the pathologic consequences of Chlamydia genital infection are well-established, the mechanisms leading to tissue damage are not completely understood. Methods: All the experiments were approved by the Ethical Committee of the University of Bologna. Animals used were 24 female Balb/c mice, 7 weeks old. All animals received medroxyprogesterone acetate 9 and 2 days prior the infection. Twelve mice were infected by placing 15 µl of sucrose-phosphate-glutamic acid (SPG) buffer containing 10 6 inclusion forming units (IFUs) of C. muridarum into the vaginal vault. Nine animals were inoculated with 15 µl of SPG containing heat-inactivated 10 6 IFUs of C. muridarum . As controls of inflammation, 3 animals were challenged with 15 µl of SPG. At 3, 10, and 20 days post-infection 4 infected animals, 3 animals inoculated with heat-inactivated bacteria and 1 control were sacrificed. Genital tracts were divided into the cervical-vaginal region, uterine horns, and oviducts. Right uterine horns and oviducts were stored in formalin and later processed for histological examinations. The remaining parts of the organs were used for RNA extraction, by using Trizol Reagent (Invitrogen), in combination with RNeasy Mini Kit (Qiagen). cDNA was synthesised with SuperScript III RT (Invitrogen). Real-time RT-PCR was performed with SYBR Green Fast Start kit (Roche Diagnostics). Primers used to assess INF-γ, TNF-α, MMP-2, MMP-9 and GAPDH levels were from SuperArray (SABiosciences). Results: At histological examination no controls showed inflammation. On the contrary, scores of inflammation in all the organs from infected animals peaked at day 10, whereas only a single animal inoculated with inactivated bacteria showed a very mild inflammation at day 10 in its uterus. At day 10, organs from infected animals showed significantly higher MMP-2 and MMP-9 genes expression than organs obtained from non-infected mice. Conclusions: Our study confirms the pivotal role of MMPs in the development of tissue damage.